Becoming Amazigh: standardisation, purity, and questions of identity. Issue 3 (26th May 2016) - Soulaimani, Dris
ABSTRACT: The status of Amazigh/Berber language and identity in Morocco has provoked multiple debates in recent years, including a debate on unifying the three main Amazigh varieties (Tashelhit, Tamazight, and Tarifit) into one standard language. This study discusses how the Amazigh language standardisation is socially constructed and profoundly connected to notions of identity, differentiation, and a pan-Amazigh imaginary. Few studies have analysed these sociolinguistic underpinnings within the framework of language ideologies. Most of these studies focus on activists working on Amazigh language issues. Drawing on theories of language ideologies and discourse analysis, this study investigates the process of Amazigh standardisation based on the views of both activists and non-activists, and discusses the social implications of this process. Informed by onsite fieldwork including questionnaire surveys and interviews, the study reveals a wide opinion divide, based on practicalities and language ideologies, between the country's Amazigh activists and non-activists. Of equal importance, the study shows that Amazigh standardisation presents a case of linguistic erasure, which negatively affects native varieties at risk of losing their local intimate qualities as mother tongues. The outcome of this study is relevant not only to Morocco, but also to other North African nations where Amazigh language issues have been drawn into social and political conflicts.